3D High‐definition anorectal manometry: Values obtained in asymptomatic volunteers, fecal incontinence and chronic constipation. Results of a prospective multicenter study (NOMAD). Issue 8 (2nd March 2017) - Mion, F.; Garros, A.; Brochard, C.; Vitton, V.; Ropert, A.; Bouvier, M.; Damon, H.; Siproudhis, L.; Roman, S.
Abstract: Background: 3D‐high definition anorectal manometry (3DARM) may aid the diagnosis of functional anorectal disorders, but data comparing asymptomatic and symptomatic subjects are scarce. We aimed to describe 3DARM values in asymptomatic volunteers and those with fecal incontinence (FI) or chronic constipation (CC), and identify which variables differentiate best these groups. Methods: Asymptomatic subjects were stratified by sex, age, and parity. Those with FI or CC were included according to anorectal symptom questionnaires. Endoanal ultrasound examination and 3DARM were performed the same day. Anal pressures were analyzed at rest, during voluntary squeeze, and during push maneuver, and compared between the 3 groups. Anal pressure defects were defined and compared to ultrasound defects. Key Results: A total of 126 subjects (113 female, mean age 52 years, range 18‐83) were included; 36 asymptomatic, 38 FI, 42 CC. Anal resting and squeeze pressures, and rectal sensitivity values were lower in FI women than in the other groups. Typical anal sphincter asymmetry during squeezing was less frequently observed in FI women. A dyssynergic pattern during push maneuver was found in 70% of asymptomatic subjects, and with a similar frequency in the 2 symptomatic groups. There was slight concordance between 3D‐pressure defects and ultrasound defects. Conclusions & Inferences: 3D anal pressures in asymptomatic women were significantly lower than in men, and in FI compared to asymptomatic women. The classical dyssynergic pattern during push maneuver was found as frequently in asymptomatic and symptomatic patients. Further studies should try to identify 3DARM variables that could reliably identify dyssynergic defecation. Abstract : Reference values for 3D high definition anorectal manometry have to be stratified by sex and age. Women with fecal incontinence have significantly lower anal pressure values than asymptomatic women. 3D high definition anorectal manometry push maneuvers do not allow to distinguish between asymptomatic and constipated women.